PROBLEMATIKA ANAK SAH DALAM PERSPEKTIF HUKUM PERKAWINAN NASIONAL DAN PUTUSAN MK NOMOR 46 TAHUN 2010 - Aisyah Rasyid (Institut Agama Islam Negeri Bone, 2021)
AbstractThis research is a study of a legitimate child in relation to the national marriage law and the Constitutional Court Decision Number 46 of 2010. The root of the problem is